2007
DOI: 10.1007/s00221-006-0826-7
|View full text |Cite
|
Sign up to set email alerts
|

The three-neuron corneal reflex circuit and modulation of second-order corneal responsive neurons

Abstract: Neurons located in the border region between the interpolaris and caudalis subdivisions of the spinal trigeminal nucleus (Vi/Vc) are second order neurons of the corneal reflex, receiving corneal afferents and projecting to the lid closing, orbicularis oculi (OO) motoneurons. Recordings of Vi/Vc neurons identified by antidromic activation from stimulation of the facial nucleus and non-identified Vi/Vc neurons reveal two neuron types, phasic and tonic. Corneal stimulation elicits Adelta latency action potentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 33 publications
9
38
0
Order By: Relevance
“…Although many spinal trigeminal neuron receptive fields appear to respond to stimulation of only one trigeminal branch, sensitization (Burstein et al, 1998;Bartsch and Goadsby, 2003) or blocking GABA receptors (Takeda et al, 2000) reveal that a single trigeminal neuron responds to both ophthalmic and maxillary trigeminal nerve branches. In the absence of sensitization, wide dynamic range trigeminal neurons in the blink circuit respond to cornea stimulation and mechanical stimulation of the periorbital and snout skin (Carstens et al, 1998;Hirata et al, 2000;Henriquez and Evinger, 2007). Thus, the presence of both ophthalmic and maxillary inputs to trigeminal neurons provides a potential substrate for associative plasticity and STDP-like mechanisms for reflex blinks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many spinal trigeminal neuron receptive fields appear to respond to stimulation of only one trigeminal branch, sensitization (Burstein et al, 1998;Bartsch and Goadsby, 2003) or blocking GABA receptors (Takeda et al, 2000) reveal that a single trigeminal neuron responds to both ophthalmic and maxillary trigeminal nerve branches. In the absence of sensitization, wide dynamic range trigeminal neurons in the blink circuit respond to cornea stimulation and mechanical stimulation of the periorbital and snout skin (Carstens et al, 1998;Hirata et al, 2000;Henriquez and Evinger, 2007). Thus, the presence of both ophthalmic and maxillary inputs to trigeminal neurons provides a potential substrate for associative plasticity and STDP-like mechanisms for reflex blinks.…”
Section: Discussionmentioning
confidence: 99%
“…First, primary afferents generate the appropriate pattern of synaptic activity in second-order trigeminal neurons to account for the pattern of suppression and facilitation seen with IO and SO temporal interactions (Lo et al, 1999). Second, single-unit recordings of second-order corneal responsive neurons in the blink circuit show that there is no decrease in the response to a second corneal stimulus, although the blink evoked by the second cornea stimulus is significantly smaller (Henriquez and Evinger, 2007). Thus, suppression of the blink evoked by the second of two identical stimuli must not occur in the second-order trigeminal neurons, but probably occurs within the reticular part of the blink circuit Zerari-Mailly et al, 2001.…”
Section: Discussionmentioning
confidence: 99%
“…10 -12 This reflex is mediated by the trigeminal and facial nerves that interact by means of polysynaptic connections in the brainstem and is not only able to initiate the protective blink reflex but directly determines the speed with which the lids close to protect the eye. 13 Because corneal sensibility is so integral to corneal health, investigative esthesiometry can be used as an indicator of corneal health. Accurate measurement of corneal sensitivity can be a reliable test of long-term corneal compromise, and strong correlations exist between sensibility and the number and density of nerves and between numbers of nerves and the number of superficial corneal epithelial cells.…”
Section: Figmentioning
confidence: 99%
“…There is no anatomical or electrophysiological evidence for a pathway, direct or indirect, from the OOMNs to the OPNs in the monkey (Langer and Kaneko 1990). Perhaps this is achieved through inhibitory relay cells similar to the inhibitory burst neurons for saccades, or some other blink-related cells causally linked to blink onset, such as the Vi/Vc group (Henriquez and Evinger 2007). Although it seems reasonable to think that these hypothetical blink-related inhibitory relay cells might be the same cells that also inhibit the LPSMNs during the closing of the eyelid, Fuchs et al (1992) reported that, for air-puff trigeminal blinks in the monkey, LPSMNs stop firing 29.2 ms, on average, before blink onset.…”
Section: Opn Pause Onsetmentioning
confidence: 99%